Leveraging ChatGPT for Rethinking Plagiarism, Digital Literacy, and the Ethics of Co-Authorship in Higher Education - Abby McGuire (Irish Journal of Technology Enhanced Learning, 2023)
Within higher education, technology has consistently influenced the writing process; however, no technology has composed and shaped the message in the same way as Large Language Model-based artificial intelligence tools. Despite the rapid adoption of generative AI tools in higher education contexts, ethical best practices for using LLMs for technology-enhanced learning experiences within higher education are still evolving. To further examine AI-based co-authorship, the ChatGPT 3.5-generated position paper featured in this article’s second section argues for redefinitions of plagiarism and co-authorship in higher education and presents implications for teaching students the necessary digital literacy skills for navigating responsible, ethical AI use. The final section of this paper presents a human-generated comparative reflection of various composing processes and technologies used to create this article and the significance of these composing processes on the craft of writing. This paper aims advance ongoing discussions about the changing nature of authorship in technology-enhanced education.